Control and resolution mechanisms of the inflammatory response - Baizabal Aguirre, Víctor M. (2014)
Inflammation is beneficial to the organism because it represents one of the first barriers against external and internal stimuli. It is a complex process in which a number of cells and molecules play different roles in a coordinated and well-controlled manner. However, a failure of the mechanism that self-regulates and resolves the process may lead to chronic inflammation, and this in turn may cause degenerative diseases such as cancer, diabetes, and autoimmune and cardiovascular diseases. Therefore, a deep knowledge about the cellular and molecular mechanisms used to resolve inflammation is mandatory to design tools and strategies to control it. This task is not easy taking into account that different signaling pathways activate several molecules involved in the resolution of the inflammatory response and some of them interfere with cellular activities unrelated to the resolution phenomenon. In addition, many reports have shown that several molecules activate or inhibit inflammation depending on the tissue or the physiological context. Furthermore, it has been observed that inhibition of several molecules considered as proinflammatory has resulted in the intensification of the inflammatory response. Having this is mind, this special issue has gathered original and review articles that will help us to expand our knowledge on the complex process of the inflammation control and resolution. More importantly, the papers presented in this special issue are a good reference to recognize what type of studies is missing and the way we could fill the gaps.